The potential of the agro-processing industry for industrialization in Zambia - Mapulanga, Willard (School of Economics, 2021)
This study investigates how the development of the agro-food processing industry could support the structural transformation of the Zambian economy. This is set against a backdrop of improved food systems coupled with increased demand for processed foods domestically and regionally, as well as income growth, urbanization, and regional integration. Developing the agro-processing sector will involve the building of dynamic industrial capabilities along with product certification and standards, packaging, logistics, and access to formal markets. Using the value chain of soya beans, the study explains how the development of such a value chain could support structural transformation. Findings suggest that there are numerous opportunities, currently underexploited, for processing soya beans into diversified products. Insights from the study reveal further opportunities to accumulate productive capabilities, both downstream and upstream to stimulate value-addition and export-led growth. Harnessing these opportunities will require specific policy support for soya beans particularly aimed at growing smallholder entry, upgrading agricultural efficiency, engaging government and non-state actors to build capacity to improve processing technologies, food testing, packaging, meeting standards and certification schemes, as well as harmonisation of regional standards.